2002
DOI: 10.1038/sj.bjc.6600228
|View full text |Cite
|
Sign up to set email alerts
|

An infectious aetiology for childhood brain tumours? Evidence from space–time clustering and seasonality analyses

Abstract: To investigate whether infections or other environmental exposures may be involved in the aetiology of childhood central nervous system tumours, we have analysed for space -time clustering and seasonality using population-based data from the North West of England for the period 1954 to 1998. Knox tests for space -time interactions between cases were applied with fixed thresholds of close in space, 55 km, and close in time, 51 year apart. Addresses at birth and diagnosis were used. Tests were repeated replacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 14 publications
5
66
2
Order By: Relevance
“…As many comparisons were made, this may be a consequence of multiple hypothesis testing. However, several factors support a genuine association: the effect was more marked in younger children and was consistent across several types of infection, and other studies have reported evidence of an infective aetiology of these tumours (Linet et al, 1996;Linos et al, 1998;Fear et al, 2001;McNally et al, 2002).…”
Section: Main Findingsmentioning
confidence: 76%
See 3 more Smart Citations
“…As many comparisons were made, this may be a consequence of multiple hypothesis testing. However, several factors support a genuine association: the effect was more marked in younger children and was consistent across several types of infection, and other studies have reported evidence of an infective aetiology of these tumours (Linet et al, 1996;Linos et al, 1998;Fear et al, 2001;McNally et al, 2002).…”
Section: Main Findingsmentioning
confidence: 76%
“…A cohort study of children born during a period of over 50 years, found space -time clustering of pilocytic astrocytoma and ependymoma in children aged 0 -4 years, suggesting that pre-natal or peri-natal exposure to infection may be a risk factor for these tumours (McNally et al, 2002). Although our study did not have enough cases to analyse by specific type, the young age distribution and preponderance of astrocytomas and ependymomas among children highly exposed to peri-natal infections were consistent with the findings of McNally et al (2002).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we subsequently reported an association between exposure around birth to high levels of population mixing and a lower risk of brain and spinal tumours and a possible association between parental migration and a higher risk of neuroblastoma (Dickinson et al, 2002b). Recent epidemiological studies have suggested that exposure to infections before or around birth may be associated with the risk of brain tumours in children (Linet et al, 1996;Linos et al, 1998;McKinney et al, 1999;Fear et al, 2001;McNally et al, 2002). In addition, it has been suggested that JC virus has a role in the aetiology of brain tumours (Khalili, 2001).…”
mentioning
confidence: 99%